2019
DOI: 10.3389/fped.2018.00405
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Abnormalities in Epstein Barr Virus Associated T/NK Lymphoproliferative Disorders

Abstract: Epstein Barr virus positive T/NK lymphoproliferative disorders (EBV-TNKLPD) comprise a spectrum of neoplasms ranging from cutaneous lymphoid proliferations to aggressive lymphomas. The spectrum includes extranodal NK/T-cell lymphoma (ENKTL), aggressive NK-cell leukemia, and a group of EBV-TNKLPDs affecting children which are poorly characterized in terms of their molecular biology. Gene and miRNA expression profiling has elucidated RNA abnormalities which impact on disease biology, classification, and treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 74 publications
1
4
0
1
Order By: Relevance
“…11 However, DDR is defective in various kinds of tumors, including NKTCL, making it an important antitumor target. 7 Consistently, a previous study of our team found that part of the DDR pathway was hindered midway in NKTCL tissues, with ATM overactivated while its downstream factors Chk2 and p53 unactivated, compared with the normal tissues. 17 The DDR defect also creates vulnerabilities in tumors and has been exploited as a target of antitumor therapy.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…11 However, DDR is defective in various kinds of tumors, including NKTCL, making it an important antitumor target. 7 Consistently, a previous study of our team found that part of the DDR pathway was hindered midway in NKTCL tissues, with ATM overactivated while its downstream factors Chk2 and p53 unactivated, compared with the normal tissues. 17 The DDR defect also creates vulnerabilities in tumors and has been exploited as a target of antitumor therapy.…”
Section: Discussionsupporting
confidence: 88%
“…6 The pathogenesis of NKTCL has not been fully understood, but the deregulation of the DNA damage response (DDR) may play a role. 7 DNA lesions occur constantly owing to the assaults of endogenous metabolites and environmental stressors. In response to DNA double-strand breaks (DSBs), the immediate-early sensors ataxia telangiectasia mutated (ATM) activates and then phosphorylates checkpoint kinase 2 (Chk2) on its Thr68 site.…”
Section: Introductionmentioning
confidence: 99%
“…EBV can cause latent infection: when an infected individual develops an immunosuppressive state, it is reactivated, which can lead to infectious mononucleosis, lymphoma, and lymphoproliferative diseases. EBV reactivation is very common after kidney transplantation and is associated with increased morbidity and mortality ( Cohen, 2000 ; Blazquez-Navarro et al., 2018 ; de Mel et al., 2018 ). In the present study, we found that the abundance of bloodstream EBV in children in PICU was positively correlated with lymphocyte subtype counts, including WBC, CD4+ T cells, CD3+ T cells, and CD8+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many scholars have made important contributions to research in EBV-related lymphoproliferative diseases, leading to breakthroughs in genomic exploration. Nonetheless, relevant studies have mostly focused on EBV T/natural killer (NK) cell lymphoproliferative diseases or chronic active EBV (CAEBV) infection [7][8][9][10], and sequencing for HVLPD has rarely been performed. HVLPD shares many common features with EBV T/NK cell lymphoproliferative diseases or CAEBV without HVLPD, including high levels of EBV DNA in the blood (primarily inTor NK cells) and a high frequency of clonal T cells.…”
Section: Introductionmentioning
confidence: 99%